Determinants of Mergers and Acquisitions Success in Banking Industry - Zhou, Yinzhi (2010)
This paper is designed to investigate why previous researches fail to detect the synergies and benefits of combination, what are the determinants of M&A success in banking industry, and to what extent can these determinants influence the post-merger performance. Multiple regression analysis is performed on a data sample of 39 M&A cases in banking industry over 2001-2009 to estimate the relationship between explanatory variables and the dependent variable.